Interfacial mass transfer intensification with highly viscous mixture. (8th June 2021) - Xie, Hanguang; Zong, Yuan; Shen, Lian; Dai, Gance
Highlights: A novel way (open windows) for mass transfer intensification. Symmetric and antisymmetric flow distributions found inside the window. Two synergetic mechanisms for mass transfer intensification. The maximum local mass transfer rate increases by 2–6.5 times. Abstract: Many investigations find that mass transfer efficiency decreases dramatically with increasing viscosity, which poses challenges to the industrial processes with the highly viscous mixture. We use liquid films on a vertical plate with windows to address this problem. The hybrid twin-liquid films combine the motility of free-falling films with the stability of wall-bounded films. In this study, the film thickness distributions are measured experimentally, and the detailed hydrodynamics and mass transfer process are studied with numerical simulations. The results reveal the hydrodynamic and mass transfer behaviors of highly viscous twin-liquid films. Due to gravity acceleration inside the window, the maximum velocity of liquid films increases by 2.5–16 times, and the maximum local mass transfer rate increases by 2–6.5 times in our simulations. We conclude that compared with conventional methods, open windows significantly enhance mass transfer in viscous liquid films without additional cost.